Pilomatrixoma: A masquerader at uncommon sites - Kanika Sharma; Minu Bajpai; Rajni Yadav; Prabudh Goel (Wolters Kluwer Medknow Publications, 2021)
The rarity, diverse clinical presentation, relatively featureless sonography, and diagnostic dilemma associated with pilomatrixomas may trigger anxiety and call for unwarranted investigations. The authors have shared their experience in two consecutive cases to generate awareness for such lesions.